If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -5x = x + -12 Reorder the terms: 7 + -5x = -12 + x Solving 7 + -5x = -12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + -5x + -1x = -12 + x + -1x Combine like terms: -5x + -1x = -6x 7 + -6x = -12 + x + -1x Combine like terms: x + -1x = 0 7 + -6x = -12 + 0 7 + -6x = -12 Add '-7' to each side of the equation. 7 + -7 + -6x = -12 + -7 Combine like terms: 7 + -7 = 0 0 + -6x = -12 + -7 -6x = -12 + -7 Combine like terms: -12 + -7 = -19 -6x = -19 Divide each side by '-6'. x = 3.166666667 Simplifying x = 3.166666667
| 2x^2-48x=0 | | (-1)x=-(-10) | | 4(6y-12)-2y=-4 | | -x+92=2x-3x | | x^2-4s+4=0 | | 16+x=-73 | | X+17-3X=11 | | 227-5x=81+19 | | 3x+38=11x-26 | | (-5)x=-(-10) | | 0.4-1.2=0.3+0.6 | | q+16=-3 | | x-(-37)=55 | | 3ln(2)-2ln(3)=0 | | 48=-4(-3x-6) | | -14=a+24 | | x=3r-12 | | 2(2n+3)=10 | | (-1)x=-10 | | 5x^2+24x+27=0 | | m-16=8 | | 3+3r-4r=-1 | | 3(10-2n)=0 | | 8+y=-7 | | 1.4f+1.1=8.3f | | 26y=32 | | 1.4f+1.1=8.3f | | 2x=-(-8) | | r^2+2r+2=0 | | 4.8=-16+1.6z | | 5(2n+1)=25 | | 0.75w+4=-3(0.75w+2)+8 |